2022
DOI: 10.3389/fcell.2022.1009908
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiological functions and clinical implications of annexin dysregulation in human cancers

Abstract: Annexins are an extensive superfamily of structurally related calcium- and phospholipid-binding proteins, largely conserved and widely distributed among species. Twelve human annexins have been identified, referred to as Annexin A1-13 (A12 remains as of yet unassigned), whose genes are spread throughout the genome on eight different chromosomes. According to their distinct tissue distribution and subcellular localization, annexins have been functionally implicated in a variety of biological processes relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 313 publications
0
8
0
Order By: Relevance
“…In addition, we observed that silencing of ANXA5 and ANXA6 has no effect on cell growth in vitro (Figure 3c). This result was surprising, since both annexins have been associated with growth‐promoting and ‐inhibiting features (Grewal et al., 2021; Prieto‐Fernández et al., 2022). Actually, we showed that sgANXA6 MDA‐MB‐231 cells proliferate more rapidly than control cells, while sgANXA5 MDA‐MB‐231 cells exhibited a slower growth than both other cell types (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we observed that silencing of ANXA5 and ANXA6 has no effect on cell growth in vitro (Figure 3c). This result was surprising, since both annexins have been associated with growth‐promoting and ‐inhibiting features (Grewal et al., 2021; Prieto‐Fernández et al., 2022). Actually, we showed that sgANXA6 MDA‐MB‐231 cells proliferate more rapidly than control cells, while sgANXA5 MDA‐MB‐231 cells exhibited a slower growth than both other cell types (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…To date, no potential therapy targeting ANXA5 or ANXA6 has been reported (Prieto‐Fernández et al., 2022). Inhibiting membrane repair of cancer cells with therapeutic antibodies would be a good option since it has been shown that a monoclonal anti‐ANXA6 antibody significantly decreases the invasiveness of pancreatic, lung, and breast cancer cells in vitro (O'Sullivan et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Annexin family members can regulate various cellular functions including vesicle trafficking, vesicle fusion, plasma membrane repair, promotion of membrane segregation and actin cytoskeleton dynamic regulation [ 63 , 64 , 65 , 66 ]. Dysregulation of annexins has been associated with multiple cancers including BC, and these proteins have emerged as potential biomarkers and pharmacological targets for medical applications [ 67 ]. Quantitative mass spectrometry-based proteomic analyses revealed significantly higher ANXA1 protein expression in more invasive glioblastoma cells [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian tissues, annexins appear widely, but variably expressed. 10,75 In human cancers normal expression patterns appear to be disrupted 75 (and see later discussion). Of course, tissues are made up not only of many different cell types, but also cells at different stages of differentiation, activity, and the cell cycle.…”
Section: Regulation Of Annexin Gene Expressionmentioning
confidence: 99%